2017
DOI: 10.1080/1461670x.2017.1360150
|View full text |Cite
|
Sign up to set email alerts
|

She Persisted … and so did He

Abstract: After years of recorded misogyny, the release of an Access Hollywood tape on 7 October 2016 revealed Trump stating he grabs women by their genitals without their permission. This study examines the gatekeeping process of traditional and online media covering this issue, focusing specifically on source use. A content analysis (N = 847) of television, newspaper, and online media shows that television and conservative sources have the highest gender disparity in source use; whereas online media focus the most on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In relation to the accusations against Donald Trump of sexual violence and misogyny, Blumell (2019) found that female sources were more likely to defend survivors and not Trump, while the opposite was true for males. Television media used male sources significantly more than print and online media, while also using female sources less; print media uses male sources significantly more than on-line, but there is no significant relationship between their use of female sources.…”
Section: Total 100% 100%mentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the accusations against Donald Trump of sexual violence and misogyny, Blumell (2019) found that female sources were more likely to defend survivors and not Trump, while the opposite was true for males. Television media used male sources significantly more than print and online media, while also using female sources less; print media uses male sources significantly more than on-line, but there is no significant relationship between their use of female sources.…”
Section: Total 100% 100%mentioning
confidence: 99%
“…"While discussion of military women in the media spiked [after the crime], their actual voices did not; 75% of articles in both newspapers did not include female sources at all". The gender of source in gender violence stories matters, as Blumell (2019) found in her analysis of stories in American cable television stations, national newspapers, and the most shared online articles related to the release of a recording of former U.S. President Donald Trump's conversation about grabbing women by their genitals: "…not only did female sources defend survivors more than male sources, there was a negative relationship with male sources and defending survivors.…”
Section: Total 100% 100%mentioning
confidence: 99%
“…Women are also more likely to be quoted as eyewitnesses or as sources sharing their personal opinions. Even when a story topic directly involves women-such as former president Trump's misogynistic acts-cable TV and conservative outlets are likely to use twice the number of female than male sources (Blumell, 2019). These differences in sourcing patterns highlight the gendered areas of expertise ascribed to men and women (Shor et al, 2015).…”
Section: The Masculine Culture Of Journalismmentioning
confidence: 99%